Contextual Dynamics of School Financial Management: Insights from SMPN 2 Baleendah and SMP Al Qona’ah - Akhmad Muhaemin; Waska Warta (At Turots: Jurnal Pendidikan Islam, 2026)
This study conducts a comparative analysis of educational financing management, guided by the Planning, Organizing, Actuating, and Controlling framework, in two distinct Indonesian educational settings: SMPN 2 Baleendah (public school) and SMP Al Qona’ah Baleendah (private school). The research employed a qualitative descriptive approach, utilizing purposive sampling to select key informants including principals, treasurers, teachers, and school committee members. Data were collected through participatory observation, in-depth interviews, and document analysis, and analyzed using the interactive model of Miles and Huberman. Findings reveal significant divergence in POAC implementation driven by institutional context, funding mechanisms, and student socioeconomic characteristics. SMPN 2 Baleendah, as a public institution, demonstrates a structured, government-regulated financial management approach primarily dependent on School Operational Assistance funds. Its planning prioritizes comprehensive development, including infrastructure, learning resources, and teacher training, with formal organizational structures and systematic control mechanisms leading to improved facilities, stable academic achievement, and high public trust. Conversely, SMP Al Qona’ah Baleendah, a private school facing funding limitations and reliance on community contributions, adopts an adaptive, community-driven model. Its planning focuses on operational survival and basic maintenance, with flexible organizational structures and actuating strategies emphasizing teacher creativity and resourcefulness. Control mechanisms are community-based, ensuring accountability despite challenges like delayed BOS disbursements, successfully maintaining learning quality and community trust. The study concludes that POAC functions are not universal but are dynamically shaped by contextual variables, with public/private status acting as a crucial intervening factor. This research offers a contextualized model of educational financing management, advancing theoretical understanding by emphasizing the indispensable role of institutional context in shaping managerial practices and providing practical implications for differentiated, effective financial governance strategies.